Pengaruh Tax Avoidance Terhadap Nilai Perusahaan Dengan Kepemilikan Institusional Sebagai Variabel Moderasi - Novantia Pancarani; Agus Athori; Miladiah Kusumaningarti (FEB Universitas Maritim Semarang, 2024)
The purpose of this study is to determine the effect of tax avoidance on firm value with institutional ownership as a moderating variable in Conventional Banking for 2021-2022. This type of research uses quantitative research because it leads to measurement methods and samples to test variables and hypotheses. Source of data in this study using secondary data. The sample in this research is 38 Conventional Banking observations in the 2021-2022 period using a purposive sampling technique. The analysis technique used is the normality test, heteroscedasticity test, autocorrelation test, t test, simple and multiple linear regression analysis, and test the coefficient of determination (R2) using the SPSS version 25 program. The results of this study state that the tax avoidance variable has a positive and significant effect on company value in the banking sector for the 2021-2022 period and company value can be explained by the Tax Avoidance variable through a regression model of 44.2%. The institutional ownership variable is able to moderate and strengthen the relationship between tax avoidance on firm value in the banking sector for the 2021-2022 period and corporate value can be explained by the Tax Avoidance variable which is moderated by the Institutional Ownership variable, namely 76.4%.